Body Fat Percentage and the Long-term Risk of Fractures. The EPIC-Norfolk Prospective Population Cohort Study. (February 2023) - Pana, Tiberiu A.; Kioh, Sheng Hui; Neal, Samuel R.; Tan, Maw Pin; Mat, Sumaiyah; Moayyeri, Alireza; Luben, Robert N.; Wareham, Nicholas J.; Khaw, Kay-Tee; Myint, Phyo K.
Highlights: We aimed to determine the association between percentage body fat and incident fractures, separately for men and women. We included 14, 129 participants from the EPIC-Norfolk Prospective Population Cohort Study. In women, a lower percentage body fat was associated with a higher risk of any fracture and specifically of hip fracture. In men, the risk of any fracture did not change with percentage body fat, while the risk of hospitalisation for a hip fracture increased with percentage body fat. These findings add to the important evidence base regarding the risk of a serious and prevalent adverse outcome. Abstract: Background: This cohort study aimed to determine the association between body fat percentage (BF%), incident fractures and calcaneal broadband ultrasound attenuation (BUA). Methods: Participants were drawn from the EPIC-Norfolk Prospective Population Cohort Study (median follow-up = 16.4 years). Cox models analysed the relationship between BF% and incident fractures (all and hip). Linear and restricted cubic spline (RCS) regressions modelled the relationship between BF% and BUA. Results: 14, 129 participants (56.2 % women) were included. There were 1283 and 537 incident all and hip fractures respectively. The participants had a mean (standard deviation) age of 61.5 (9.0) years for women and 62.9 (9.0) years for men. Amongst men, BF% was not associated with incident all fractures. While BF% < 23 % (median) was not associated with hip fractures, BF% > 23 % was associated with increased risk of hip fractures by up to 50 % (hazard ratio (95 % confidence interval) = 1.49 (1.06–2.12)). In women, BF% < 39 % (median) was associated with up to 32 % higher risk of all fractures (1.32 (1.13–1.44)), while BF% > 35 % was not associated with this outcome. Higher BF% was associated with lower risk of incident hip fractures in women. Higher BF% was associated with higher BUA amongst women. Higher BF% up to 23 % was associated with higher BUA amongst men. Conclusions: Higher BF% is associated with lower risk of fractures in women. While there was no association between BF% and all fractures in men, increasing BF% >23 % was associated with higher risk of hip fractures in men. This appears to be independent of estimated bone mineral density. Fracture prevention efforts need to consider wider physical, clinical, and environmental factors.